Hedgehog lipids: Promotors of alternative morphogen release and signaling?: Conflicting findings on lipidated Hedgehog transport and signaling can be explained by alternative regulated mechanisms to release the morphogen. (5th October 2021) - Manikowski, Dominique; Ehring, Kristina; Gude, Fabian; Jakobs, Petra; Froese, Jurij; Grobe, Kay
Abstract: Two posttranslational lipid modifications present on all Hedgehog (Hh) morphogens—an N‐terminal palmitate and a C‐terminal cholesterol—are established and essential regulators of Hh biofunction. Yet, for several decades, the question of exactly how both lipids contribute to Hh signaling remained obscure. Recently, cryogenic electron microscopy revealed different modes by which one or both lipids may contribute directly to Hh binding and signaling to its receptor Patched1 (Ptc). Some of these modes demand that the established release factor Dispatched1 (Disp) extracts dual‐lipidated Hh from the cell surface, and that another known upstream signaling modulator called Scube2 chaperones the dual‐lipidated morphogen to Ptc. By mechanistically and biochemically aligning this concept with established in vivo and recent in vitro findings, this reflection identifies remaining questions in lipidated Hh transport and evaluates additional mechanisms of Disp‐ and Scube2‐regulated release of a second bioactive Hh fraction that has one or both lipids removed. Abstract : Dually lipidated Sonic Hedgehog (Shh) must be removed from the plasma membrane of producing cells before it can signal to distant receiving cells that express the Shh receptor Patched1. Here we discuss suggested mechanisms to release differently lipidated Shh variants with different Patched1‐binding properties from the same dually lipidated precursor.